Comparative study between two empirical antibiotic regime in the management of childhood malignancy with fever - Helaly, Laila; Sarker, Md Zakir Hossain; Mannan, MA; Hossain, Md Tafazzal; Ahmed, Shafi; Begum, Momtaj (Northern International Medical College Journal, 2015)
Objective : The present prospective randomized clinical trial was carried out to assess whether combined cefepime and amikacin as empirical antibiotic therapy was more effective than combined ceftriaxone and gentamicin in the treatment of febrile neutropenic children with malignant diseases. Material & Methods : The study was conducted in the Pediatric Hematology and Oncology unit of BSMMU over a period of 2 years. (From January 2006 to December 2007) Hospitalised pediatric cancer patients who developed febrile neutropenia following chemotherapy or radiotherapy were the study population. A total 64 cases were consecutively included in the study and were randomly assigned to either cefepime & amikacin group (Group- A) or ceftriaxone & gentamicin group (Group-B). The Group-A received cefepime 1500 mg/m2/dose infused over 15 minutes in two divided doses intravenously(IV) while amikacin was administered as thrice daily dose of 200 mg/m2/dose. Patients of Group-B received ceftriaxone 1500 mg/m2/dose in two divided doses and gentamicin 60 mg/m2/dose thrice daily IV. The therapy was continued until absolute neutrophil counts reached >1000 neutrophils/mm3. The treatment outcome was considered successful if fever resolves within 4 days and does not recur within 7 days of completion of therapy. Of the 64 patients, 13 cases were excluded from the final analysis. Results : Bacteria were isolated from culture in only 16.7% of cases Group-A and 9.5% of group-B. Patients E. coli was the most common isolate found in blood specimen (37%). Following intervention, 90% of cefepime & amikacin group and 85.6% of ceftriaxone & gentamicin group improved absolute neutrophil count to >1000/mm3 of blood. Persistence of fever after start of study drug and duration of antibiotic therapy were significantly less in the former group than those in later group (p = 0.049 and p = 0.004 respectively). Only 1 patient of group B had recurrence of infection within 7 days of treatment completion. The mean duration of hospital stay was less in the former group (7.97 ± 2.61 days) than that in the latter group (11.00 ± 3.42 days) (p = 0.06). Evaluation of final outcome shows that majority (86.6%) of cefepime & amikacin group had successful outcome, while majority of ceftriaxone & gentamicin group (81%) failed to resolve infection with continuation of fever for > 4 days. Conclusion : The study concluded that combined cefepime and amikacin is a better option for empirical treatment of fever and neutropenia in children with malignancies than combined ceftriaxone and gentamicin (p<0.001). Northern International Medical College Journal Vol.5(2) 2014: 329-331